Fault-Tolerant Resolvability in Some Classes of Line Graphs. (26th September 2020) - Guo, Xuan; Faheem, Muhammad; Zahid, Zohaib; Nazeer, Waqas; Li, Jingjng
Abstract : Fault tolerance is the characteristic of a system that permits it to carry on its intended operations in case of the failure of one of its units. Such a system is known as the fault-tolerant self-stable system. In graph theory, if we remove any vertex in a resolving set, then the resulting set is also a resolving set, called the fault-tolerant resolving set, and its minimum cardinality is called the fault-tolerant metric dimension. In this paper, we determine the fault-tolerant resolvability in line graphs. As a main result, we computed the fault-tolerant metric dimension of line graphs of necklace and prism graphs (2010 Mathematics Subject Classification: 05C78).